(untitled) (International Journal of Engineering and Computer Science, 2015)
MYCIN was the one of the initial expert systems to perform with the level of expertise of a human expert and to provide users with complete explanation of its logical reasoning. MYCIN played a benchmark of most of the expert systems which were developed after MYCIN. Moreover, the techniques which were developed for MYCIN expert system have become most widely available design in the various small expert system building tools. It was designed to aid doctors in proper diagnosis and treatment of bacteremia infections. MYCIN was strictly a research system. The present paper provides summary of rule application concepts of MYCIN expert system.